If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (12x + -11)(8x + -5) = 0 Reorder the terms: (-11 + 12x)(8x + -5) = 0 Reorder the terms: (-11 + 12x)(-5 + 8x) = 0 Multiply (-11 + 12x) * (-5 + 8x) (-11(-5 + 8x) + 12x * (-5 + 8x)) = 0 ((-5 * -11 + 8x * -11) + 12x * (-5 + 8x)) = 0 ((55 + -88x) + 12x * (-5 + 8x)) = 0 (55 + -88x + (-5 * 12x + 8x * 12x)) = 0 (55 + -88x + (-60x + 96x2)) = 0 Combine like terms: -88x + -60x = -148x (55 + -148x + 96x2) = 0 Solving 55 + -148x + 96x2 = 0 Solving for variable 'x'. Factor a trinomial. (5 + -8x)(11 + -12x) = 0Subproblem 1
Set the factor '(5 + -8x)' equal to zero and attempt to solve: Simplifying 5 + -8x = 0 Solving 5 + -8x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -8x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -8x = 0 + -5 -8x = 0 + -5 Combine like terms: 0 + -5 = -5 -8x = -5 Divide each side by '-8'. x = 0.625 Simplifying x = 0.625Subproblem 2
Set the factor '(11 + -12x)' equal to zero and attempt to solve: Simplifying 11 + -12x = 0 Solving 11 + -12x = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -12x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -12x = 0 + -11 -12x = 0 + -11 Combine like terms: 0 + -11 = -11 -12x = -11 Divide each side by '-12'. x = 0.9166666667 Simplifying x = 0.9166666667Solution
x = {0.625, 0.9166666667}
| 3x^2+7x-11=-5x+4 | | x+38=-42 | | 118-4x=4x+14 | | -16x+92=-42 | | 1-y=6 | | 0.2x+1=0 | | -4b-28=0 | | t-(-10)=-8 | | 7x-2y=31 | | 7-63x=12 | | -5-b=2a | | 3x^2-14x=-3 | | -5-b= | | (u)3-7u-6ifu=-2 | | -5-6=2a | | 12x+90=85 | | a+3b=-2 | | 7(y-6)=28 | | 5.6+10.5=2.1A | | 8x^2+22x=-5 | | 11x-20=7x-64 | | -(1-7x)-6(-7-x)=36 | | 7x+35=-21 | | 13+2d+4d+3d+9= | | -16b=9 | | y=x^2-6x-3 | | 26+b=20 | | -8x-9x=.66 | | 2a=18 | | 12=x^2-6x | | 3x+9-x=15 | | 36x^2-9x=0 |